Pengaruh Persediaan Bahan Baku Terhadap Proses Produksi pada PT Indoprima Gemilang Gresik - Putri Ainur Rosidah; Zaman, Komarun; Megasari, Aisyah Darti (ProBisnis : Jurnal Manajemen, 2024)
Optimal management is needed because raw material inventory is a very important business asset in supporting production activities. Business actors must be able to regulate their material supply standards so that they are not too big and not too small. Businesses can achieve effective inventory control through inventory spending to help the business achieve its goals. The aim of this research is to identify and evaluate raw material inventory control for the production process that has been implemented. This research uses qualitative methods to support previous research on how the role of raw material inventory is important in the course of the production process to enable businesses to minimize inventory expenditure and meet consumer needs in a timely manner, thereby achieving their goals.